Estimation of productivity and sowing qualities of the winter bread wheat varieties of the FSBSI “ARC “Donskoy” in the primary seed production - Yu. G. Skvortsova; G. A. Filenko; T. I. Firsova; N. G. Chertkova; N. V. Kalinina (Зерновое хозяйство России)
The production of winter wheat varieties, which are characterized by high productivity and sowing qualities of seeds, is one of the ways to improve productivity and gross grain harvest in the region. The current paper has presented data on the productivity, sowing qualities and biological properties of the original seeds of the winter bread wheat varieties ‘Stanichnaya’, ‘Lydia’ and ‘Asket’, grown in the laboratory for primary seed production of the Federal State Budgetary Scientific Institution “ARC “Donskoy”. The purpose of the research was to study the productivity and sowing qualities of the winter bread wheat varieties. Productivity is the main criterion for the value of a variety. It was found that with an average productivity (5.8 t/ha) of the variety ‘Stanichnaya’, the data by the years of 2018–2020 varied from 5.1 to 7.2 t/ha, and for the variety ‘Asket’, at a similar level of average value, the variation ranged from 5.2 to 6.8 t/ha. There was found that 1000-seed weight depended on the variety and climatic conditions, and not only on the cultivation technology. The leader in this indicator was the variety ‘Stanichnaya’, with an average value (44.5g) of 1000-seed weight. The maximum yield of conditioned seeds during the years of research was identified in the varieties ‘Stanichnaya’ (73.5%) and ‘Lydia’ (72.4%); the minimum was in the variety ‘Asket’ (71.7%). There was noted that the germination energy of the varieties ‘Stanichnaya’, ‘Lidiya’ and ‘Asket’ ranged from 88 to 92%. The difference between germination energy and laboratory germination ranged from 5 to 8%. When determining the intensity of the initial growth, it was found that the maximum values of the sprout length and weight of 100 dry sprouts were identified in the variety ‘Stanichnaya’ (11.0 cm and 0.63 g); the smallest values of these traits were identified in the varieties ‘Lydia’ and ‘Asket’. Field germination varied by the varieties from 73 to 82%, deviations of this trait from laboratory germination ranged from 14 to 23%. Over the years of study, for all studied varieties, the sowing qualities of seeds corresponded to GOST R 52325-2005.